Teacher's Display and Referential Questions (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
This paper discusses an English teacher's display and referential questions in teaching speaking at MAN 3 MALANG. It investigated the ways teacher employed display and referential questions, students' responses, and the ways the questions maintained communication in the classroom. The observations in several meetings were applied and were confirmed by the instructional objectives stated in lesson plans and syllabus. It was found that the teacher mostly employed referential questions rather than display questions in teaching speaking. The employment of display questions was put in the beginning of the lesson and was functioned as ice breaker or warmer. Through display and referential questions, the communication in teaching speaking was maintained. It suggests that the teacher applies questioning strategies in employing referential questions so that the communication in the classroom is well-maintained.